Formation of arbitration courts in Uzbekistan and development prospects - X.T.Odilqoriev (Zien Journals, 2022)
This article is named “Formation of arbitration courts in Uzbekistan and the prospects for development". In the scientific work, the latest innovations in legislative norms and stages of development have been highlighted and researched. Also, examples and views of the role of arbitration courts are described by the author
Keywords: arbitration; court; legislation; disputes